Putting occupational science evidence into action: Contributions from the field of implementation science. - Donnelly, Miranda R.; Liew, Sook-Lei; Jolles, Mónica Pérez (Journal of Occupational Science, 2026)
Knowledge generated in occupational science has been envisioned as having transformative potential for societal change, especially in supporting and empowering under-resourced communities. However, a key gap in occupational science scholarship is translating evidence so it can be used to address real-world problems. The field of implementation science was established to address knowledge-to-practice gaps in a variety of disciplines facing this challenge. In this commentary, we discuss how implementation science can contribute to closing the knowledge-to-practice gap in occupational science, with a focus on how implementation science can support alignment between applied evidence in occupational science and the contexts in which it can be used to inform multi-level practices. We propose that collaborations between occupational science and implementation science scholars could enhance the pragmatic value of occupational science findings by helping move occupational science evidence about occupation and its relationship to well-being and health from research arenas to real-world contexts where it could have an outsized impact.